1992
DOI: 10.1213/00000539-199207000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Human Immunodeficiency Virus in Surgeons, Anesthesiologists, and Medical Students

Abstract: We postulated that three factors determined the occupational risk of infection from the human immunodeficiency virus (HIV) for surgeons, anesthesiologists, and medical students: first, the risk of needlestick exposure per year (range for surgeons 3.8-6.2, weighted average 4.2; range for anesthesiologists 0.86-2.5, weighted average 1.3; range for third-year medical students 0-5, best estimate 5); second, the risk of seroconversion from a needlestick exposure (0.42%-0.50%); and third, prevalence of HIV in the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Similar findings were reported from HCW studied at the National Institutes of Health (5). By using published data, Buergler et al (6) calculated that the I-yr risk of needlestick-acquired HIV infection for an anesthesiologist ranged from 0.002% to 0.129%. Reduction of this risk for anesthesia providers requires strategies to eliminate or reduce needle usage specific to the practice of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were reported from HCW studied at the National Institutes of Health (5). By using published data, Buergler et al (6) calculated that the I-yr risk of needlestick-acquired HIV infection for an anesthesiologist ranged from 0.002% to 0.129%. Reduction of this risk for anesthesia providers requires strategies to eliminate or reduce needle usage specific to the practice of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies of health care workers (HCW) exposed to HIV-infected material have shown that the risk of transmission is greater after percutaneous injuries, such as accidental needlesticks, than with intact skin or mucous membrane contact (4,5). Buergler et al (6) have pointed out that three factors determine the annual risk of occupational infection with HIV 1) the annual risk for a needlestick injury; 2) the risk of seroconversion after a needlestick exposure; and 3) the prevalence of HIV infection in the specific patient population. Only one of these factors, the risk of an accidental needlestick, can be easily modified by HCW in an attempt to reduce the incidence of occupation-related infections.…”
mentioning
confidence: 99%
“…Deep subcutaneous or intramuscular exposure to a blood‐contaminated needle from a patient with high HIV viraemia appears to be the worst type of contact [11]. Three factors determine the occupational risk of HIV infection for health workers: first, the risk of needlestick exposure per year, secondly, the risk of seroconversion from a needlestick exposure; and thirdly, the prevalence of HIV in the population served [12]. Most contaminated percutaneous injuries occur during multistep procedures, during recapping of needles or when contaminated sharps are not discarded safely [13].…”
Section: Modes Of Transmissionmentioning
confidence: 99%
“…The cumulative risk (R) for occupational HIV conversion of a surgeon in the course of his professional career has been calculated 13,17,28 from the HIV prevalence among the patients treated (P), the number of parenteral exposures to patients' blood (E), and the seroconversion rate after a single parenteral exposure (S). Based on a seroconversion rate of 0.3%, a surgeon operating over a period of 40 years on patients with a seroprevalence of 0.5% and having an average of ten percutaneous blood contacts per year, has a cumulative risk of 0.6% according to the equation: R = P ϫ E ϫ S = 0.005 ϫ (40 ϫ 10) ϫ 0.003 = 0.006…”
mentioning
confidence: 99%